A randomized study comparing the use of a pelvic lead shield during trans‐radial interventions: Threefold decrease in radiation to the operator but double exposure to the patient. Issue 7 (3rd February 2015) - Musallam, Anees; Volis, Ina; Dadaev, Svetlana; Abergel, Eitan; Soni, Amit; Yalonetsky, Sergey; Kerner, Arthur; Roguin, Ariel
<x xml:space="preserve">Abstract</x> Objectives To determine the efficacy of a 0.5‐mm lead apron across the patient's abdomen in addition to standard operator protection for the reduction of scatter radiation on operator and patient radiation exposure Background Cardiac angiography using the radial access compared to the femoral approach is associated with reduced complication rate and improved patient comfort but has significantly increased radiation dose. Improvements in radiation protection are needed Methods We randomly assigned 332 patients undergoing coronary angiography to a group with pelvic lead shielding and a group with standard protection. In each procedure, eight digital dosimeters were used to measure operator radiation dose [under the lead apron, outside the thyroid shield, and at the left side of the head], patient dose at the level of the umbilicus [above and beneath the lead apron], and two on the acrylic shielding and one on the image receptor to measure scattered radiation Results Both groups were similar in BMI, procedures performed, and number of sequences. Usage of lead shielding statistically significantly reduced the radiation dose of the operator at all three sites measured: under lead apron [all in µSv]: 0.53 ± 1.4 vs. 0.17 ± 0.6, on thyroid collar 5.9 ± 7.7 vs. 2.9 ± 3.4, and left side of head 3.3 ± 3.4 vs. 2.1 ± 2.2, P < 0.001. However the radiation to the patient was doubled from 15.4 ± 24.1 to 28.9 ± 81.1, P = 0.04 Conclusions The use of a pelvic lead shield during radial angiography reduced the operator radiation exposure at multiple measurement sites. However there was an increased exposure to the patient. This balance should be further investigated before the widespread adoption of this method. © 2015 Wiley Periodicals, Inc.